Systemic Sarcoidosis Presenting with Headache and Stroke-Like Episodes. (29th September 2015) - Campbell, J.; Kee, R.; Bhattacharya, D.; Flynn, P.; McCarron, M.; Fulton, A.
Abstract : Sarcoidosis is a multisystem granulomatous disorder. Neurological manifestations as a presenting symptom are relatively rare. A 26-year-old male presented with a five-week history of headache suggestive of raised intracranial pressure. He subsequently developed transient episodes of mild right-sided hemiparesis and numbness. Magnetic resonance imaging (MRI) of brain revealed widespread inflammatory white matter lesions, an ischaemic focus in the left corona radiata, and widespread microhaemorrhages consistent with a more diffuse vasculopathy. Serum angiotensin-converting enzyme (ACE) level was normal. Lumbar puncture revealed an elevated opening pressure (36 cmH2 O) and inflammatory cerebrospinal fluid (CSF). Computerised tomography (CT) of chest, abdomen, and pelvis revealed widespread lymphadenopathy and biopsy of axillary lymph nodes revealed the presence of noncaseating granulomata in keeping with systemic sarcoidosis. The patient responded well to corticosteroids. This case highlights the importance of considering sarcoidosis to be a rare but potentially treatable cause of stroke in younger patients.